Production of a fuel gas by fluidised bed coal gasification compatible with CO2 capture. (1st January 2020) - Spiegl, Nicolas; Berrueco, Cesar; Long, Xiangyi; Paterson, Nigel; Millan, Marcos
Highlights: Significant changes in performance can be achieved by altering operating conditions. High carbon conversions achieved in CO2 and CO2 /steam fluidized bed gasification. Medium LHV gas was reached from gasification in CO2 even in the absence of steam. Carbon conversion was sensitive to CO2 /C ratio at 850 °C but not at 750 or 950 °C. Replacing 25% CO2 by steam enabled a 100 °C drop without loss in carbon conversion. Abstract: A continuously fed, laboratory scale spouted bed gasifier has been used to study oxy-fuel gasification of German lignite. In this paper, the influence of different gasification agents and bed temperature on the process performance, during tests at atmospheric and elevated pressure are studied. Two gasification agents have been used, CO2 (with different CO2 /C ratios) and mixtures of CO2 /steam. The results show that despite the relatively slow CO2 -char reaction, good gasification performance could be achieved with German lignite by adjusting the operating conditions at atmospheric pressure: complete carbon conversion, high energy conversion and a medium heating value fuel gas (8–10 MJ m −3 ). The CO2 /C ratio was found to have a large effect on the gasification performance. Increasing the ratio increased the carbon conversion, but the CO2 conversion decreased. At 950 °C, maximum carbon conversion was already achieved with pure CO2, therefore using steam at this temperature could not increase the conversion, but did increase the H2 /CO ratio in the fuel gas. At 850 °C, replacing 25% of CO2 with steam increased the carbon conversion to the level achieved at 950 °C without steam. Replacing more than 25% of CO2 with steam increased the H2 /CO ratio further. Therefore, with the addition of steam, the operating temperature could be reduced from 950 °C to 850 °C while maintaining the gasification performance. The changes of gasification performance with steam addition at pressures up to 10 bara followed the same trends achieved at atmospheric pressure.